Pattern of distribution of oral cancer by site in relation to habits among patients attending Cancer Institute, Maharagama. - Gamage, N.T (My University, 1993)
Oral cancer is a public health problem in the South Asian region, including Sri Lanka, because of its high prevalence. Usually oral cancer does not appear "de novo" and it is preceded by a precancerous lesion or condition. Seventy five percent of floor of the mouth cancer were detected among alcoholic patients those who consume alcohol only. With increasing the frequency of betel chewing (number per day ) the risk of inflicting buccal mucosal cancer also increased. Highest precentage of buccal mucosal cancer (69 per cent) was found among those who kept the quid in the mouth overnight